2017
DOI: 10.1038/nature24649
|View full text |Cite|
|
Sign up to set email alerts
|

PD-1 is a haploinsufficient suppressor of T cell lymphomagenesis

Abstract: T cell non-Hodgkin lymphomas (T-NHLs) represent a heterogeneous group of highly aggressive malignancies with poor clinical outcomes1. T-NHLs originate from peripheral T lymphocytes and are frequently characterized by genetic gain-of-function variants in T cell antigen receptor (TCR) signalling molecules1–4. Although these oncogenic alterations are thought to drive TCR pathways to induce chronic proliferation and survival programmes, it remains unclear whether T cells harbour tumour suppressors that can counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
152
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 40 publications
9
152
0
Order By: Relevance
“…However, caution must be exercised with such approaches as these inhibitory receptors are part of physiological processes involved in modulating T-cell activity, and permanently unleashing T cells with no feedback and attenuation mechanisms may increase the risk of toxicity owing to uncontrolled activation. Importantly, recent work demonstrated that PD-1 is a tumour suppressor gene, raising the possibility that deletion of PD-1 in engineered T cells could ultimately increase the risk of malignant transformation 157 .…”
Section: Nature Biomedical Engineeringmentioning
confidence: 99%
“…However, caution must be exercised with such approaches as these inhibitory receptors are part of physiological processes involved in modulating T-cell activity, and permanently unleashing T cells with no feedback and attenuation mechanisms may increase the risk of toxicity owing to uncontrolled activation. Importantly, recent work demonstrated that PD-1 is a tumour suppressor gene, raising the possibility that deletion of PD-1 in engineered T cells could ultimately increase the risk of malignant transformation 157 .…”
Section: Nature Biomedical Engineeringmentioning
confidence: 99%
“…PD-1 blockade in these models seems to promote PI3K/AKT activity and tumor growth. PI3K/AKT is the target of PI3K-inhibitors like duvelisib, that have recently demonstrated good activity in TCL (43, 44). It seems evident that the use of checkpoint inhibitors in TCL with oncogenically activated TCR pathways needs to be preceded by some special considerations(43).…”
Section: Immune System In T Cell Neoplasms – Rationale For Immunotherapymentioning
confidence: 99%
“…As such, anti-PD-1 treatment triggers an immune response, b , Wartewig et al . 1 have demonstrated that PD-1 signalling in a mouse model of T cell non-Hodgkin’s lymphoma prevents proliferation of cancerous T cells (the source of the PD-1 ligand was not defined). In these mice, anti-PD-1 treatment can aggravate disease by reactivating the cancerous cells to enable their continuous proliferation.…”
Section: Figure 1|mentioning
confidence: 99%
“…Wartewig et al . 1 report on page 121 that a widely used cancer immunotherapy actively promotes tumour progression in a mouse model of a cancer called T-cell non-Hodgkin’s lymphoma (T-NHL).…”
mentioning
confidence: 99%